Abundance and biomass of tintinnids (Protozoa, Ciliophora) in Brandsfield Strait in March 2002 - N. A. Gavrilova (Ukrainian Antarctic Journal, 2004)
Absract. Taxonomy, abundance and biomass of tintinnids from the Bransfield Strait were investigated during 7-th Ukrainian Antarctic Expedition (March, 2002). 7 species of tintinnids were found in the samples. Cymatocylis affins/convallaria dominated in terms of abundance (3373 cells/m3) and biomass (0,64 mgWW/m3). The highest total tintinnid abundance (5622 cells/m3) and biomass (1,06 mg WW/m3) were recorded at the stations distant from the Antarctic Peninsula, while in the coastal waters tintinnids were not found. It was noticed that tintinnid communituy depend on level of phytoplankton development, hydrodynamical and hydrochemical conditions in the Bransfield Strait during March 2002.